Letter from the World Veteran Federation to Kádár's Government on the Trial of Gen. Maléter and Associates - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): World Veteran Federation According to this letter, the trials are illegal because Gen. Maléter and associates were arrested while performing their duties as representatives of the elected Hungarian government. The association pleads for international disclosure.